Effects of water network dependency on the electric network for post-earthquake fire suppression. Issue 5 (2nd September 2020) - Coar, Maxwell; Garlock, Maria; Elhami Khorasani, Negar
ABSTRACT: This article provides insights to the community-level evaluation of post-earthquake fire suppression capability considering the performance of a water network and its dependence on the electric network. The objective is to examine the effects of three parameters on post-earthquake water availability at fire hydrants: water network design, seismic hazard, and electric network dependency scenario. Results show that topology-based and energy-based network performance metrics need to be used in conjunction with water source performance for accurate representation of network behavior. Ignoring explicit dependence of the water network on the electric network may provide inaccurate and unconservative predictions of available water pressure and flow at fire hydrants. This is particularly true for "medium" to "large" seismic events. Additionally, there may be a quantifiable level of dependence that a water network has on power before dependent analysis is necessary, perhaps as simple a metric as total head available from energy-dependent sources.